Aprender é preciso? Criação e invenção na aprendizagem inventiva e na aprendizagem baseada na solução de problemas - Coelho, Rômulo Frota da Justa (2011)
This dissertation aims at showing that the concept of Inventive Learning brings new contributions to the context of educational psychologies, renewing the field by guaranteeing a theoretical framework to a series of learning processes that have been traditionally denied or relegated to a non-scientific category. We focused on researching the innovative potential of Inventive Learning within creative processes in human cognition. We take in consideration processes such as intuition, distraction, invention, phenomena that cross us, and make us learners not always on an organized and precise fashion. Finally, we point out some topics to be explored by later studies, such as a deeper analysis of the relationship between memory and the irruption of the new in an inventive context. If inventing is to "invenire", to stir up existing archaeological remains to evoke newness, what is the real role of the pre-acquired knowledge of the subject, how do they influence the emergence of invention? How is it possible to be unusually astonished by the emergence of innovation when the new creative experience it is notborn "ex-nihilo"? We also allude to fundamental questions about the frontiers of Inventive Learning and how it could be applied, in addition to typically creative activities (be it artistic, playful, philosophical ...), but also to more specific learning, such as training and procedures that require mechanical repetitions